1998
DOI: 10.1002/pro.5560070405
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of recombinant human tissue kallikrein at 2.0 Å resolution

Abstract: Human tissue kallikrein, a trypsin-like serine protease involved in blood pressure regulation and inflammation processes, was expressed in a deglycosylated form at high levels in Pichia pastoris, purified, and crystallized. The crystal structure at 2.0 8, resolution is described and compared with that of porcine kallikrein and of other trypsin-like proteases. The active and S1 sites (nomenclature of Schechter I, Berger A, 1967, Biochem Biophys Res Commun 27:157-162) are similar to those of porcine kallikrein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…In agreement with our results, other studies (16,17) using synthetic peptides showed that human tissue kallikrein displays substrate specificity for Arg, Met, and Phe with lesser specificity for Leu and Lys at the P1 position. The low selectivity of human tissue kallikrein for the P1 residue could be explained by an enlarged S1 site of tissue kallikrein, which may accommodate various amino acids as revealed by x-ray crystallography (25,26). The limited proteolytic nature of tissue kallikrein to its physiological substrates would, therefore, require other subsites in the reactive crevice to regulate the enzymatic specificity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In agreement with our results, other studies (16,17) using synthetic peptides showed that human tissue kallikrein displays substrate specificity for Arg, Met, and Phe with lesser specificity for Leu and Lys at the P1 position. The low selectivity of human tissue kallikrein for the P1 residue could be explained by an enlarged S1 site of tissue kallikrein, which may accommodate various amino acids as revealed by x-ray crystallography (25,26). The limited proteolytic nature of tissue kallikrein to its physiological substrates would, therefore, require other subsites in the reactive crevice to regulate the enzymatic specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular Modeling of Human Tissue Kallikrein-The atomic coordinates of the x-ray structure of human tissue kallikrein were generously provided by Dr. Katz (26). The coordinates of the "kallikrein loop," consisting of 14 residues from 95 [102] to 98K [115], are not available in this molecular model.…”
Section: P1 P2 and P3 Specificity Of Kallistatinmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to KLK1 expressed in Escherichia coli, natural urinary KLK1 was confirmed to be glycosylated, as well as the variant expressed in the yeast Pichia pastoris (Angermann et al, 1989;Chan et al, 1998). This expression system with heterogeneous glycosylation caused problems in crystallization of human KLK1, even after enzymatic deglycosylation, requiring the mutation of the sequons for a successful X-ray structure determination (Katz et al, 1998). In the crystal structure of human apo-KLK1 only a single GlcNAc at Asn95 was visible in the electron density, despite the presence of up to three GlcNAc 2 Man 3 (Fuc) trees (Figure 3) (Laxmikanthan et al, 2005).…”
Section: Current Status Of Glyco-klk Site Analysis Tissue Kallikrein mentioning
confidence: 96%